KONSEP PENDIDIKAN INKLUSIF PERSPEKTIF AL-QUR’AN: TELAAH QS ABASA AYAT 1-11 - Asep Samsul Umam (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2025)
Backgrounded by the fact that education is a basic need for every human being, yet some individuals do not receive adequate education. Children who exhibit physical differences, different abilities, and attitudes from the general population often face discrimination in the education system. Building a tolerant attitude will be effective if it is done through inclusive education in schools. The concept of inclusive education in Islamic teachings is found in the Qur'an, which explains that humans on earth are created with various races, tribes, nations, genders, religions, and abilities, in order to recognize, appreciate, and respect each other regardless of their differences. In this scientific work, the researcher uses the library research method by tracing various references related to the topic of discussion, which is an analysis of the concept of inclusive education in the Qur'an, Surah Abasa verses 1-11. By understanding the values of the concept of inclusive education in the Qur'an, it is possible to build social tolerance regardless of differences. Where equitable education can enable all children to have the opportunity to participate fully in regular activities regardless of disabilities